2011
DOI: 10.1158/1940-6207.capr-10-0361
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Imbalances between Screen- and Symptom-Detected Breast Cancers and Impact on Disease-Free Survival

Abstract: Background Screening mammography results in the increased detection of indolent tumors. We hypothesized that screen and symptom-detected tumors would show genotypic differences as copy number imbalances (CNIs) that in part explain differences in the clinical behavior between screen and symptom-detected breast tumors. Methods We evaluated 850 women aged ≥ 40 diagnosed with stage I–II breast cancer at the MD Anderson Cancer Center between 1985 to 2000 with information available on method of tumor detection (sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…CNAs are frequently identified in breast tumours (>90%)29 30 with particular types of aberrations associated with specific subtypes of breast cancers 30–32. For example, Letessier et al 32 reported frequent amplification of chromosomal regions 8p12, 8q24, 11q13, 17q12 and 20q13 in breast cancers, and in particular, 12p13 amplification was associated with basal molecular type.…”
Section: Discussionmentioning
confidence: 99%
“…CNAs are frequently identified in breast tumours (>90%)29 30 with particular types of aberrations associated with specific subtypes of breast cancers 30–32. For example, Letessier et al 32 reported frequent amplification of chromosomal regions 8p12, 8q24, 11q13, 17q12 and 20q13 in breast cancers, and in particular, 12p13 amplification was associated with basal molecular type.…”
Section: Discussionmentioning
confidence: 99%
“…We would expect these tumors to become large enough to be self-palpated prior to being detected on screening mammography. This expectation is reflected in the finding that symptom-detected breast cancers have more copy number imbalances, which is associated with more aggressive behavior [59]. Thus, the screening process is biased to detect less aggressive tumors that do not progress to an invasive state.…”
Section: Discussionmentioning
confidence: 99%
“…High copy number gains were 41.2 and homozygous deletions o − 1.2. Segmented copy number data were also obtained from published studies [17][18][19] and imported into Nexus. Copy number thresholds of ± 0.2 were used for the invasive cohorts to take into account the higher level of normal cell contamination.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…(a) Frequency plots of copy number gain (blue) and loss (red) in pure DCIS, DCIS synchronous with invasive breast cancer and invasive breast cancer. 17 Below are difference plots comparing pure DCIS with invasive breast cancer and pure DCIS with DCIS synchronous to invasive breast cancer. Blue line is the difference in gain frequency; red is the difference in loss frequency.…”
Section: Er Status Is Associated With Different Copy Number Changes Imentioning
confidence: 99%